A proteomic atlas of insulin signalling reveals tissue‐specific mechanisms of longevity assurance. Issue 9 (15th September 2017) - Tain, Luke S; Sehlke, Robert; Jain, Chirag; Chokkalingam, Manopriya; Nagaraj, Nagarjuna; Essers, Paul; Rassner, Mark; Grönke, Sebastian; Froelich, Jenny; Dieterich, Christoph; Mann, Matthias; Alic, Nazif; et al.
Abstract: Lowered activity of the insulin/IGF signalling (IIS) network can ameliorate the effects of ageing in laboratory animals and, possibly, humans. Although transcriptome remodelling in long‐lived IIS mutants has been extensively documented, the causal mechanisms contributing to extended lifespan, particularly in specific tissues, remain unclear. We have characterized the proteomes of four key insulin‐sensitive tissues in a long‐lived Drosophila IIS mutant and control, and detected 44% of the predicted proteome (6, 085 proteins). Expression of ribosome‐associated proteins in the fat body was reduced in the mutant, with a corresponding, tissue‐specific reduction in translation. Expression of mitochondrial electron transport chain proteins in fat body was increased, leading to increased respiration, which was necessary for IIS‐mediated lifespan extension, and alone sufficient to mediate it. Proteasomal subunits showed altered expression in IIS mutant gut, and gut‐specific over‐expression of the RPN6 proteasomal subunit, was sufficient to increase proteasomal activity and extend lifespan, whilst inhibition of proteasome activity abolished IIS‐mediated longevity. Our study thus uncovered strikingly tissue‐specific responses of cellular processes to lowered IIS acting in concert to ameliorate ageing. Synopsis: Proteomic analyses of four key insulin‐sensitive tissues in a long‐lived Drosophila insulin/IGF signalling mutant identify key tissue‐specific processes that regulate lifespan. The proteomes of the brain, gut, fat body and muscle tissues from insulin/IGF signalling mutant Drosophila are profiled. Responses to reduced insulin/IGF signaling are highly tissue‐specific, influencing different processes in different tissues. Increased fat body‐specific mitochondrial biogenesis and respiration are both necessary and sufficient to extend lifespan. Increased gut‐specific proteasomal assembly and activity are both necessary and sufficient to extend lifespan. Abstract : Proteomic analyses of four key insulin‐sensitive tissues in a long‐lived Drosophila insulin/IGF signalling mutant identify key tissue‐specific processes that regulate lifespan.